Chosen-key extracting attack to random LSB steganography - CHEN Jia-yong1; ZHU Yue-fei1; ZHANG Wei-ming2; LIU Jiu-fen2 (Tongxin xuebao)
A chosen-key extracting attack based on random LSB steganography was proposed.By constructing an orient ring model for a sort of pseudo-random steganography algorithms,it proved that there are many equivalent keys and neighboring keys in the model,and then proposed a method to calculate the number of equivalent keys.With the charac-ter of equivalent keys,neighboring keys and outlier detection method,the proposed scheme achieved lower computational complexity than the method proposed by Fridrich.Both academic results and experimental results indicated that the algorithm was reliable even with rather big error in estimating the embedding rate.